2018
DOI: 10.1587/transinf.2017mvp0010
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Peak Estimation for Real-Time 3D Ping-Pong Ball Tracking with Double-Queue Based GPU Acceleration

Abstract: 3D ball tracking is of great significance in ping-pong game analysis, which can be utilized to applications such as TV contents and tactic analysis, with some of them requiring real-time implementation. This paper proposes a CPU-GPU platform based Particle Filter for multiview ball tracking including 4 proposals. The multi-peak estimation and the ball-like observation model are proposed in the algorithm design. The multi-peak estimation aims at obtaining a precise ball position in case the particles' likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As to the chosen algorithm, because of the prohibitively large number of simulations which is also known as particles, the extreme large computation complexity is shown as a problem in achieving real-time performances. An extension work [24] of the chosen algorithm [9] on ping-pong ball tracking and its accelerated work [28] have shown that algorithms basis on particle filter have large potential for acceleration. Basing on the characteristic of ping-pong ball during games, work [24] makes some improvements in the observation and the resampling algorithms of the chosen one [9] which are not friendly to other ball games.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the chosen algorithm, because of the prohibitively large number of simulations which is also known as particles, the extreme large computation complexity is shown as a problem in achieving real-time performances. An extension work [24] of the chosen algorithm [9] on ping-pong ball tracking and its accelerated work [28] have shown that algorithms basis on particle filter have large potential for acceleration. Basing on the characteristic of ping-pong ball during games, work [24] makes some improvements in the observation and the resampling algorithms of the chosen one [9] which are not friendly to other ball games.…”
Section: Introductionmentioning
confidence: 99%
“…Basing on the characteristic of ping-pong ball during games, work [24] makes some improvements in the observation and the resampling algorithms of the chosen one [9] which are not friendly to other ball games. What's more, the modification has caused a considerable distinction in accelerated structure [28] on GPU system which means that it [28] cannot be applied in the acceleration of the chosen algorithm [9]. The goal of this research is implementing a 3D ball tracking system to obtain both high accuracy and real-time realization based on the chosen algorithm [9].…”
Section: Introductionmentioning
confidence: 99%